ISU GLOBAL PEREKONOMIAN ISLAM: Telaah Kritis terhadap Tata Kelola dan Aktivitas Lembaga-lembaga Keuangan Islam - Muhdi Kholil (Universitas Alma Ata, 2011)
Indonesia is to be known widely by the world, which has Islamic finance system different from most countries. Indonesia which is in the international forum of financial syriah known